If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1h + -45 = 21 Reorder the terms: -45 + 1h = 21 Solving -45 + 1h = 21 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 1h = 21 + 45 Combine like terms: -45 + 45 = 0 0 + 1h = 21 + 45 1h = 21 + 45 Combine like terms: 21 + 45 = 66 1h = 66 Divide each side by '1'. h = 66 Simplifying h = 66
| -5+4(5x-4)=-4x-21 | | -5+4(5x-4)=4x-21 | | 4x^2-676= | | k-5+4=k-4k-1 | | 9(c-1)=45 | | 3-(2x-3)=-8x+2(4+3x) | | x+(x(.15))=7.61 | | x(2)+y=25 | | 4a+(4a+3)= | | 2=4r+6 | | 3(4x-3)=2x-5 | | 0=x^2+8x+4 | | 4s+-8=16 | | 7x-3y=3 | | .5x+1.15=1.65 | | 1x-2x=20 | | r+2=5r+6 | | x(2)+4x=12 | | x(2)+6x=-8 | | 2v+18=16-4(v-7) | | x^3+8x^2+21x+8=0 | | 9x^3+8x^2+18x+12=0 | | 2x+8=18 | | 8h+4=3h-4 | | x^4+8x^3+21x^2+18x=0 | | (x+y)2=x+xy+y | | 14(t-2)+7t=7(3t+5)-13 | | 49=30-k/16 | | 4x+6y=21 | | 4x-1=2+X | | (2x-5y)-(2x+5y)= | | X^3-21x+10=0 |